2022
DOI: 10.1093/brain/awac109
|View full text |Cite
|
Sign up to set email alerts
|

Trigeminal microvascular decompression for short-lasting unilateral neuralgiform headache attacks

Abstract: A significant proportion of patients with short-lasting unilateral neuralgiform headache attacks (SUNHA) are refractory to medical treatments. Neuroimaging studies have suggested a role for ipsilateral trigeminal neurovascular conflict with morphological changes in the pathophysiology of this disorder. We present the outcome of an uncontrolled open-label prospective single centre study conducted between 2012 and 2020, to evaluate the efficacy and safety of trigeminal microvascular decompression in refractory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…All patients had exhausted other treatments with a median of 7 preventive medications trialled prior to MVD. Partially skewed by the scale of the Lambru et al 30 study, MVD had the longest postoperative surveillance interval with a mean follow-up of 42.4 months.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…All patients had exhausted other treatments with a median of 7 preventive medications trialled prior to MVD. Partially skewed by the scale of the Lambru et al 30 study, MVD had the longest postoperative surveillance interval with a mean follow-up of 42.4 months.…”
Section: Resultsmentioning
confidence: 95%
“…Notably, Lambru et al 30 recently published their results from a large prospective study where they evaluated the role of MVD in 47 SUNCT/SUNA patients with MRI evidence of ipsilateral neurovascular conflict. Participants had failed to benefit from a mean of 8 preventive medications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have explored the characteristics of, and relationship between, SUNCT and SUNA [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Some specialists have suggested that the classifications should be revised.…”
Section: Open Accessmentioning
confidence: 99%
“…Trigeminal neurovascular conflict in short-lasting unilateral neuralgiform headache attacks has been seen in the past with conflicting results when these neurovascular conflicts were treated 32,33 ; however, a recent study explored the long-term efficacy of microvascular decompression of the trigeminal nerve in patients described as having medication-refractory SUNHA, and 78.7% of the 47 patients had a good or excellent response. 34 Whether the outcome is more a reflection of some misdiagnosis of trigeminal neuralgia as SUNHA in the first instance, combined with SUNHA with nerve irritation, is an open question. It is likely that just as SUNHA has pain triggerable from cutaneous stimulation that trigeminal nerve irritation would produce the same clinical picture.…”
Section: (►Table 2)mentioning
confidence: 99%